Estudo longitudinal da função ventricular esquerda de pacientes com Lipodistrofia generalizada congênita através da técnica ecocardiográfica bidimensional com Speckle tracking - Olegário, Natália Bitar da Cunha (2022)
Congenital Generalized Lipodystrophy (CGL) is a rare autosomal recessive disease characterized by the total or almost total absence of subcutaneous adipose tissue. The syndrome may present with leptin deficiency, severe insulin resistance, diabetes mellitus, dyslipidemia, hepatic steatosis, premature atherosclerosis and systemic arterial hypertension, conditions recognized as important cardiovascular risk factors. Studies that point to disorders in the structure and function of the heart used the two-dimensional method for echocardiographic evaluation, however, the technique of studying myocardial deformation by two-dimensional speckle-tracking (ST2D) is more sensitive in the investigation of left ventricular function. Objective: To evaluate the evolution of left ventricular function in patients with Congenital Generalized Lipodystrophy. Methods: A longitudinal study was carried out from January 2016 to January 2022, with all patients with CGL being followed up at the Lipodystrophies Outpatient Clinic of the University Hospital of the Federal University of Ceará/Ebserh. Following a follow-up clinical protocol, all participants who underwent a two-dimensional ECHO and a ST2D on two occasions were included. This technique performed the measurement of global longitudinal strain (SGL), obtained by evaluating the mean strain value of the 18 left ventricular segments in the three standard apical views. Biochemical evaluation and molecular study of patients with the syndrome were also performed. Results: Of the 23 patients with LCG in follow-up, 20 patients who underwent 2 exams were included in the study, with a mean interval between exams of 51±16.4 months. Such patients had a mean age of 14.7 ± 11.2 years, 60% were female, 15 with CGL type 1 and 5 with CGL type 2. All patients had hypoleptinemia, 60% had low HDL-c, 55 % hypertriglyceridemia, 85% diabetes, 45% hypercholesterolemia and 20% systemic arterial hypertension (SAH). When comparing the two-dimensional ECHO data, there was an increase in LV systolic and diastolic volume between the two assessments, in the group younger than 18 years. As for the assessments of patients older than 18 years, worsening of LV ejection fraction and increase in left atrial diastolic volume were found. In the first evaluation using the ST2D technique, 60% (n=12) of the patients had reduced SGL. The most recent evaluation showed reduced SGL values in 65% (n=13) of patients with CGL, of whom 23% (n=3) had a mutation in the BCLS2 gene. A correlation was found between the SGL and the variables glycemia and glycohemoglobin A1c. Conclusions: In this study, it was possible to demonstrate, in a large series of predominantly young patients with congenital generalized lipodystrophy, early and subclinical changes in left ventricular function, using the two-dimensional speckle-tracking technique, with diastolic dysfunction being observed in 35% of the patients at the time of second evaluation. In the longitudinal evaluation, the first described in patients with this condition, performed at a mean interval of 51±16.4 months, there was evidence of worsening of the ejection fraction through the two-dimensional echocardiogram, although no worsening of strain values was observed. There was, however, an association between the progression of subclinical cardiac alterations and poor glycemic control (HbA1c and glycemia), with the diagnosis of diabetes being related to the reduction of the longitudinal global strain.